The Influence of Profitability Ratio on the Company Value of Bank OCBC TBK - Sri Handayani, Azizah; Rosmawati, Siti (Coopetition : Jurnal Ilmiah Manajemen, 2025)
This study aims to examine the impact of profitability ratios, using the variables Return on Assets (ROA) and Net Profit Margin (NPM) on company value using the Price Earning Ratio (PER). In this study, the multiple linear regression analysis method was applied with company data taken from the OCBC Bank company website. The results of the study stated that there was no significant effect between the profitability ratio (ROA and NPM) on company value. These findings can be concluded that although profitability has an important role in describing financial performance, there are various aspects that can affect the value of a company. This study also provides a new perspective on the complex relationship between financial performance and company value, as well as the importance of considering other variables in analyzing companies.